Prednosti in slabosti beta testiranja - Dogša, Tomaž (Uporabna informatika (Ljubljana), 1996)
In this paper we discuss testing problems of software intended for many unknown users. Firstly we analyse correctness, usability testing and beta testing. The results show that beta testing is a very promising method. Finally, a comparison between beta and traditional testing method is made. The results of comparison between beta and traditional testing method is made.The results of comparison support the objectiveness of decision about including beta testing in the V&V (verification and validation) plan.
Keywords: beta testiranje; programska oprema; testiranje